2017
DOI: 10.1093/jee/tox116
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Long-Term Mass Rearing of Neoseiulus californicus (Acari: Phytoseiidae) on Almond Pollen

Abstract: Long-term feeding effects of the almond pollen on the life table parameters of Neoseiulus californicus McGregor were assessed after 5, 10, and 20 generations after introduction in the rearing arena. Furthermore, to evaluate behavioral characteristics of the mass-reared predator (strain A) in face with the real prey, functional and numerical responses of the predator to different densities of the twospotted spider mite nymphs were determined, and the obtained data were compared with those reared on twospotted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 23 publications
2
29
1
Order By: Relevance
“…Alireza Nemati and Elham Riahi food diets (e.g., Nguyen et al, 2014;Khanamani et al, 2017). Furthermore, the results of the current study showed that the daily predation rate of A. swirskii mass-reared on maize pollen was considerably lower compared to natural prey and almond pollen diets, which may be due to the longer handling time and the lower attack rate estimated by the model (tables 5, 7).…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…Alireza Nemati and Elham Riahi food diets (e.g., Nguyen et al, 2014;Khanamani et al, 2017). Furthermore, the results of the current study showed that the daily predation rate of A. swirskii mass-reared on maize pollen was considerably lower compared to natural prey and almond pollen diets, which may be due to the longer handling time and the lower attack rate estimated by the model (tables 5, 7).…”
mentioning
confidence: 50%
“…Furthermore, the individuals of strains A and T consumed the same number of prey during the period of 24 h at different prey densities. In other studies, Khanamani et al (2017) found that the predation rate of N. californicus was the same between individuals mass-reared on almond pollen and T. urticae at lower prey densities. Nguyen et al (2014), who explored predation rates of A. swirskii on immature Frankliniella occidentalis (Pergande) reared on five different diets over six generations, found that most diets had no effect.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, they showed a lower adult emergence rate and fecundity in the wasps reared in vitro compared with those reared in vivo . A number of other studies have demonstrated the importance of such quality control in the success of biological control agents reared for a long time in laboratory or insectary conditions and the subsequent sustainability of the biological control program (Miyatake, 1998; Bellutti, 2011; Khanamani et al ., 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…The predatory bug Orius spp. has been frequently shown to be able to reproduce and develop on a sole diet of specific pollen (Fauvel, 1974;Naranjo and Gibson, Ouyang et al, 1992;Van Rijn and Tanigoshi, 1999a;Bouras and Papadoulis, 2005;Papadopoulos and Papadoulis, 2008;Kolokytha et al, 2011;Khanamani et al, 2017 Amazonian Ouyang et al, 1992;Van Rijn and Tanigoshi, 1999a;Broufas and Koveos, 2000;Papadopoulos and Papadoulis, 2008;Kolokytha et al, 2011;Delisle et al, 2015a,b Apricot Saito and Mori, 1975;Overmeer, 1981;Englert and Maixner, 1988;Grout and Richards, 1992;Engel and Ohnesorge, 1994;Kostiainen and Hoy, 1994;Schausberger, 1997;Van Rijn and Tanigoshi, 1999a;Addison et al, 2000;Goleva et al, 2015;Ferreira et al, 2020 Bitter Sabelis, 1990;Van Rijn and Tanigoshi, 1999a;Nomikou et al, 2001 Castor Dosse, 1961;McMurtry and Scriven, 1964;McMurtry and Johnson, 1965;Rasmy and El-Banhawy, 1975;Momen and El-Saway, 1993;Tanigoshi et al, 1993;Yue et al, 1994;…”
Section: Pollenmentioning
confidence: 99%